The impact of digital integration on corporate sustainability: Emissions reduction, environmental innovation, and resource efficiency in the European - Majdi Anwar Quttainah; Imen Ayadi (Journal of Innovation & Knowledge (JIK), 2024)
This study examines the impact of digital integration on the environmental sustainability of European companies from 2016 to 2022, focusing on emissions reduction, environmental innovation, and resource efficiency. Using a two-stage system generalized method of moments (GMM) model and quantile regression with instrumental variables on panel data, we investigate how digital technologies influence corporate sustainability practices. Descriptive statistics reveal significant variation in digital technology adoption and environmental performance among the 22 European countries studied. Pearson's correlation matrix and variance inflation factor analyses confirm the absence of multicollinearity among the variables. The empirical results from the two-stage GMM model demonstrate that digital integration positively affects emissions reduction, environmental innovation, and resource efficiency. These findings are consistent across different quantiles, indicating that digital integration benefits companies regardless of their initial sustainability levels. However, the impact is more pronounced for companies with lower initial performance. The Hansen test validates the instruments used, and the absence of second-order serial correlation supports the robustness of our GMM model estimations. The positive relationship between past and current sustainability performance underscores the dynamic nature of corporate environmental practices. Our study highlights the crucial role of digital integration in promoting sustainable business practices and offers significant implications for policymakers and business managers. Companies are encouraged to assess their digital environmental footprints, invest in sustainable technologies, and adopt green innovations. Policymakers should support the development of digital industries and facilitate their integration into traditional sectors to enhance overall sustainability. The findings contribute to understanding how digital transformation can drive environmental sustainability, providing a foundation for future research on the intersection of digital technologies and corporate sustainability practices.
Keywords: O00; O32; Q56; D83; 650; Digital integration; Corporate sustainability; European context; GMM; IV-QRPD regression